If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + -3p = 2(6p + 5) Reorder the terms: 40 + -3p = 2(5 + 6p) 40 + -3p = (5 * 2 + 6p * 2) 40 + -3p = (10 + 12p) Solving 40 + -3p = 10 + 12p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-12p' to each side of the equation. 40 + -3p + -12p = 10 + 12p + -12p Combine like terms: -3p + -12p = -15p 40 + -15p = 10 + 12p + -12p Combine like terms: 12p + -12p = 0 40 + -15p = 10 + 0 40 + -15p = 10 Add '-40' to each side of the equation. 40 + -40 + -15p = 10 + -40 Combine like terms: 40 + -40 = 0 0 + -15p = 10 + -40 -15p = 10 + -40 Combine like terms: 10 + -40 = -30 -15p = -30 Divide each side by '-15'. p = 2 Simplifying p = 2
| -29-6y=2(4y+9) | | x + ky = 7 | | 3(5x-2)=2(3x-6) | | -26-p=7(6-5p) | | 16-8p-6p=7p-8+3p | | 3(x+1)+2x=x | | 2a-8=-12 | | -7(1-7x)=-7+3x | | 2.50x+1.75y=15 | | 2m-nx=x+4-2n | | 7x-39-4x=0 | | f(-5)=4x-1 | | 180=-15m | | 2x+(x+3)+(x-1)=42 | | 49a^2-81b^4= | | .15x-.03=.2x+1.2 | | sin(1.2x)=1 | | -9x+12+4(3x-3)=6(x-2)-4x+14 | | s=l-q | | 5x-6y-7=0 | | -3w+8=-20 | | 12-5m=3 | | .10x=.35x | | y+(0)=5 | | -6+2(p+7)=-20+6p | | 5m+21=8m-3 | | -4.9x^2-43.4x-6.3=0 | | 7x-8x+24=1 | | 7(7k-7)-1=38+5k | | 4d-3d=29 | | 6-3r=r*2 | | 4x^2+8x-2=8x+6 |